Labour Migration in the Enlarged EU: A New Economic Geography Approach - d'Artis Kancs (Economics and Econometrics Research Institute (EERI), 2011)
The paper studies the impact of migration policy liberalisation on international labour migration in the enlarged EU in a structural NEG approach. The liberalisation of migration policy would induce additional 1.80 - 2.98 percent of the total EU workforce to change their country of location, with most of migrant workers relocating from the East to the West. The average net migration rate is decreasing in the level of integration, suggesting that from the economic point of view no regulatory policy responses are necessary to labour migration in the enlarged EU.
Keywords: F12; F14; F16; J21; J61; L11; 330; Labour Migration; Economic Integration; Economic Geography; Market Access